Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
y-(12*x^2-9*x+4)=0
Step by step solution :<span>Step 1 :</span><span>Equation at the end of step 1 :</span><span> y - (((22•3x2) - 9x) + 4) = 0
</span><span>Step 2 :</span><span>Equation at the end of step 2 :</span><span> y - 12x2 + 9x - 4 = 0
</span><span>Step 3 :</span>Solving a Single Variable Equation :
<span> 3.1 </span> Solve <span> <span>y-12x2+9x-4</span> </span> = 0
In this type of equations, having more than one variable (unknown), you have to specify for which variable you want the equation solved.
Answer:
Answer to the following question is a follows;
Step-by-step explanation:
The following are a few examples of how South Africa's competitiveness policy has been successful:
⇒ Consumers or buyers were given a variety of product options as well as competitive prices.
⇒ In 1984, practises like horizontal cooperation and resale price maintenance and control were ruled illegal.
A standard algorithm is a step-by-step way to solve a problem.
Answer:
3.24m
Step-by-step explanation:
SOH
sin(26)=O/7.4
O=7.4 sin(26)
O=3.24 (3sf)
Answer:
x = -4 ;
Step-by-step explanation:
6(x+3)=2(2x+5)
Distribution
6x+18 = 4x + 10
Subtract 4x on both sides
2x+18 = 10
Subtract 18 on both sides
2x = -8
Divided by 2
x = -4
Now if we have to substitute the value of X
6(-4+3)=2(-8+5)
Parenthesis first
6(-1) = 2(-3)
-6 = -6